eLearning among Canadian anesthesia residents: a survey of podcast use and content needs - Matava, Clyde T; Rosen, Derek; Siu, Eric; Bould, Dylan M (Université d'Ottawa | University of Ottawa, 2013)
Podcasts are increasingly being used in medical education. In this study, we conducted a survey of Canadian anesthesia residents to better delineate the content needs, format preferences, and usage patterns among anesthesia residents.
Keywords: Podcasts; Residents; e-learning; Survey; Needs; Content; Anesthesia